Informational and Structural - Parametric Models of Inductions Micromotors - Mohammad, A.; Sotnik, S.; Belova, N.; Lyashenko, V. (IOSR, 2018)
Inductions motors play an important role in various areas of their application. Especially important among such engines are inductions micromotors. The breadth of use of inductions micromotors necessitates the construction of various models for such engines in order to determine the parameters of their design and operation characteristics. The article reviews the designs of existing inductions motors. An information and structural-parametric model for determining the design of inductions micromotors and their main characteristics are proposed. Calculations have been performed for one of the modifications of an inductions micromotor. The effectiveness of the proposed features modification an inductions micromotor is shown. The reliability and efficiency of the developed models for determining the design of the considered modification of an inductions micromotor is shown.
Keywords: Winding; Stator